Alaska - Sainsbury, Brendan; Bodry, Catherine; Karlin, Adam; Sainsbury, Brendan ({Not Specific}: Lonely Planet, 2022)
Lonely Planet's Alaska is our most comprehensive guide that extensively covers all that Alaska has to offer, with recommendations for both popular and lesser-known experiences. Hike the history-laden Chilkoot Trail, spot icebergs and wildlife in Glacier Bay and marvel at the majesty of the Northern Lights; all with your trusted travel companion.
Keywords: Alaska -- Guidebooks